Effects of Rainfall on the Motorway Traffic Parameters - Sándor, Zs. (Acta Technica Jaurinensis, 2013)
The relationship between traffic events and weather has been studied for over 60 years. During the last decades, several experts have analyzed the effects of weather on traffic and accidents in the world however in Hungary, such research has not been conducted yet. In this paper, the author examines the effects of rain on travel speed. The speed changes in traffic lanes (fast lane and slow lane) have been studied in different motorway cross sections with various traffic characteristics under heterogeneous traffic intensities and weather conditions.